The Relationship Between Cognitive Dissonance with Conceptual Knowledge and Environmental Literacy in Elementary School Students - Halimatussadiah, Ade Ima; Marlina, Irma; Rahman, Nuning Nurfadilah Hayati (CV. Akademi Merdeka, 2025)
This study investigates the influence of cognitive dissonance on environmental literacy and conceptual knowledge among elementary school students in the context of science learning about animal life cycles. Employing a descriptive quantitative approach with an ex post facto design, the research involved 240 students from grades 4, 5, and 6 at two elementary schools in Cirebon, Indonesia, who had received instruction on animal life cycles in accordance with the Merdeka Curriculum. Data were collected using validated and reliable four-point Likert scale questionnaires measuring environmental literacy, conceptual knowledge, and cognitive dissonance. Multivariate analysis of variance (MANOVA) was conducted to examine the relationships among these variables following the instructional intervention. The results demonstrate that students possess high levels of environmental literacy and sound conceptual understanding of animal life cycles, while experiencing moderate to low levels of cognitive dissonance. Statistical analysis reveals that science instruction incorporating cognitive dissonance significantly enhances both environmental literacy and conceptual knowledge, without inducing excessive cognitive conflict. Theoretically, this research advances the understanding of cognitive dissonance as a catalyst for meaningful learning and conceptual change in elementary science education. Practically, the findings recommend the implementation of science teaching strategies that actively challenge students’ preconceptions through real-world content, such as animal life cycles, to foster scientific literacy and environmental responsibility from an early age.